Οι εξαμηνιαίες λογιστικές καταστάσεις ως στοιχείο πρόβλεψης για τα ετήσια αποτελέσματα - Μάναλης Γκίκας Γ. (SPOUDAI Journal of Economics and Business, 2000)
Recently there is growing interest in emerging capital markets such as Athens Stock Exchange (ASE). The paper investigates the predictive content of semi-annually published earnings for the listed companies in the ASE over the period 1988-1997. By observing correlation matrices between semi-annual and annual earnings we are concerned to see if any regularities can be discovered. The degree of deviation between them is measured by calculating changes of semi-annual and yearly earnings. Different forecast errors measures such as the Mean Absolute Error, the Mean Square Error and the Average Error are used to provide evidence of the disparities of the forecast errors. The results, indicate that interim reports as currently prepared cannot predict accurately the annual earnings. Since the introduction of the measures the predictive power of semi-annual reports has been improved only marginally. JEL Classification: G 14